The Korean War and US-Indonesia Relations, 1950-1954 (Journal of International Studies, 2015)
The Korean War, which broke out very closely upon the heels of the Communist victory in China, immediately assumed global implications beyond the boundaries of the Korean Peninsula. Essentially a Korean civil war, it immediately became a major ‘hot war’ in the Cold War in Asia. This paper discusses the relations between the United States and Indonesia in the aftermath of the North Korean attack on South Korea, covering the period from the outbreak of the war in 1950 through to the end of the war in 1954. The paper explores the various ways in which the United States attempted to co-opt and coerce Indonesia into the Western camp in the Cold War, and Indonesia’s responses thereto. The central theme of the paper is the interplay between the United States’ policy of containment and the Indonesian policy of non-alignment in the Cold War. An examination of the United States’ policy toward Indonesia, a non-communist but non-aligned nation, vis-à-vis the Korean War, would serve to illustrate the dynamics and nature of the Cold War in Southeast Asia.